Noise Sources of Combined Heat and Power Plants and Methods for Noise Estimation in Adjacent Urban Areas. Issue 4 (March 2021) - Gusev, V; Ledenev, V; Antonov, A; Matveeva, I
Abstract: Combined heat and power plants (CHP) are permanently operating enterprises for the production of electrical and thermal energy. They are located, as a rule, in cities and in large settlements, create significant noise pollution for the buildings adjacent to them. Protection from the noise of the territories adjacent to the heat and power plants, especially residential buildings, is a topical scientific and practical problem. Based on the results of field measurements, the article identifies and shows the main external sources of noise that determine the noise impact of the heat and power plants on the environment of the metropolis. Such sources include large-sized ground and above-ground equipment: air intake of blower fans and chimneys, transformers, gas distribution unites, gas pipelines, cooling towers. Reliable basic data on their acoustic power and the required amount of noise reduction have a special role for the development of optimal protection from the point of view of acoustics and economics from the noise of such sources. They can only be determined by calculation for a number of equipment sources of combined heat and power plants. The article presents new, computational methods that allow you to determine the desired data and, accordingly, to qualitatively design the necessary acoustic building noise reduction tools based on the methods of shielding, sound insulation and sound absorption.